2020
DOI: 10.1128/aac.01168-20
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Controlled Cohort Study of the Impact of Glucocorticoid Treatment in SARS-CoV-2 Infection Mortality

Abstract: Background: Evidence to support the use of steroids in COVID-19 pneumonia is lacking. We aim to determine the impact of steroid use in COVID-19 pneumonia in-hospital mortality. Patients and Methods: We performed a single-center retrospective cohort study in a University hospital in Madrid, Spain, during March 2020. To determine the role of steroids in in-hospital mortality, patients admitted with SARS-CoV-2 pneumonia and treated with steroids were compared to patients not treated with steroids, adjusting by a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
120
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(135 citation statements)
references
References 21 publications
11
120
3
1
Order By: Relevance
“…[33] Fernandez-Cruz et al reported lower mortality in patients with COVID-19 pneumonia complicated with ARDS and/or a hyperin ammatory syndrome treated with corticosteroids (HR 0.36, 95% CI 0.14 to 0.93, p=0.04). [46] In the other four studies, no signi cant difference in mortality rates between steroid and non-steroid groups, [36,40,48] or even an increased risk in the group that received corticosteroids was demonstrated. [50] However, Lu et al did note that every increase of 10 mg in hydrocortisone equivalent dosage was associated with a 4% elevation of the mortality risk (HR 1.04, 95% CI 1.01-1.07).…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…[33] Fernandez-Cruz et al reported lower mortality in patients with COVID-19 pneumonia complicated with ARDS and/or a hyperin ammatory syndrome treated with corticosteroids (HR 0.36, 95% CI 0.14 to 0.93, p=0.04). [46] In the other four studies, no signi cant difference in mortality rates between steroid and non-steroid groups, [36,40,48] or even an increased risk in the group that received corticosteroids was demonstrated. [50] However, Lu et al did note that every increase of 10 mg in hydrocortisone equivalent dosage was associated with a 4% elevation of the mortality risk (HR 1.04, 95% CI 1.01-1.07).…”
Section: Resultsmentioning
confidence: 87%
“…[42,43] In the remaining eight studies, the risk of corticosteroid use was quanti ed, and these were included to calculate the pooled estimate. [23,33,36,37,40,46,48,50] The overall pooled estimate (observational studies and the RCT) showed a favorable outcome in the corticosteroid group (relative risks RR 0.55, 95% CI 0.27-0.83, random effects) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations